Function of mesenchymal stem cells following loading of gold nanotracers - et al (Dove Medical Press, 2011)
Laura M Ricles1, Seung Yun Nam1,2, Konstantin Sokolov3,1, Stanislav Y Emelianov1,3, Laura J Suggs11Department of Biomedical Engineering, 2Department of Electrical and Computer Engineering, The University of Texas at Austin, Austin, TX, USA; 3Department of Imaging Physics, The University of Texas MD Anderson Cancer Center, Houston, TX, USABackground: Stem cells can differentiate into multiple cell types, and therefore can be used for cellular therapies, including tissue repair. However, the participation of stem cells in tissue repair and neovascularization is not well understood. Therefore, implementing a noninvasive, long-term imaging technique to track stem cells in vivo is needed to obtain a better understanding of the wound healing response. Generally, we are interested in developing an imaging approach to track mesenchymal stem cells (MSCs) in vivo after delivery via a polyethylene glycol modified fibrin matrix (PEGylated fibrin matrix) using MSCs loaded with gold nanoparticles as nanotracers. The objective of the current study was to assess the effects of loading MSCs with gold nanoparticles on cellular function.Methods: In this study, we utilized various gold nanoparticle formulations by varying size and surface coatings and assessed the efficiency of cell labeling using darkfield microscopy. We hypothesized that loading cells with gold nanotracers would not significantly alter cell function due to the inert and biocompatible characteristics of gold. The effect of nanoparticle loading on cell viability and cytotoxicity was analyzed using a LIVE/DEAD stain and an MTT assay. The ability of MSCs to differentiate into adipocytes and osteocytes after nanoparticle loading was also examined. In addition, nanoparticle loading and retention over time was assessed using inductively coupled plasma mass spectrometry (ICP-MS).Conclusion: Our results demonstrate that loading MSCs with gold nanotracers does not alter cell function and, based on the ICP-MS results, long-term imaging and tracking of MSCs is feasible. These findings strengthen the possibility of imaging MSCs in vivo, such as with optical or photoacoustic imaging, to understand better the participation and role of MSCs in neovascularization.Keywords: neovascularization, gold nanoparticles, cell tracking, stem cells, fibrin gel, optical imaging